1998
DOI: 10.1002/macp.1998.021990511
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic oxidative polymerization of bisphenol-a to a new class of soluble polyphenol

Abstract: SUMMARY Enzymatic oxidative polymerization of bisphenol-A was carried out in an aqueous organic solvent using horseradish and soybean peroxidases (HRP and SBP, respectively) as catalysts. The SBP-catalyzed polymerization in an equivolume mixture of methanol and phosphate buffer (pH 7.0) affords a new class of polyphenol quantitatively, which is readily soluble in polar organic solvents such as acetone, methanol, N,Ndimethylformamide, and dimethyl sulfoxide, but insoluble in chloroform, diethyl ether, and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Oligomers such as those reported are commonly produced in enzyme-catalysed polymerizations of phenols [347][348][349] including 1a. [350][351][352][353][354] The initial step is often proposed to be a one-electron oxidation of the AH 2 or AH − forms of 1a to produce phenolate radicals which can then couple to give higher molecular weight products. [350][351][352][353][354] Our study mirrors the enzymatic results.…”
Section: Mechanistically Relevant Acid-base and Redox Properties Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligomers such as those reported are commonly produced in enzyme-catalysed polymerizations of phenols [347][348][349] including 1a. [350][351][352][353][354] The initial step is often proposed to be a one-electron oxidation of the AH 2 or AH − forms of 1a to produce phenolate radicals which can then couple to give higher molecular weight products. [350][351][352][353][354] Our study mirrors the enzymatic results.…”
Section: Mechanistically Relevant Acid-base and Redox Properties Ofmentioning
confidence: 99%
“…[350][351][352][353][354] The initial step is often proposed to be a one-electron oxidation of the AH 2 or AH − forms of 1a to produce phenolate radicals which can then couple to give higher molecular weight products. [350][351][352][353][354] Our study mirrors the enzymatic results. There is little doubt that the oxidation starts with 1-electron oxidation of either AH 2 or AH − forms of 1a.…”
Section: Mechanistically Relevant Acid-base and Redox Properties Ofmentioning
confidence: 99%
“…Research in the polymerization of phenol derivatives has also used HRP [231][232][233][234][235] and lacasse [236][237][238] as catalytic enzymes. Of interest for this review is the polymerization of caffeic acid, which is found in the phenolic compounds of potato waste.…”
Section: Enzymatic Oxidativementioning
confidence: 99%
“…PDHDPE has the same characteristic hydroxyl groups as its monomer DHDPE, which has the ability to form intermolecular hydrogen bonds with PCL. The polymer has better thermostability than the monomer in the process, since enzymatically polymerized polyphenol can be thermally cured at appropriate temperature under vacuum 13. It is reasonable to expect that the addition of PDHDPE would greatly improve the Young's modulus of PCL, if a miscible blend system was achieved.…”
Section: Introductionmentioning
confidence: 99%